Design and analysis of switched reluctance motor with FEM based Ansys-Maxwell - Yıldırım Özüpak (MANAS: Journal of Engineering)
In this study, radial forces that create noise, which is a fundamental problem in Switched Reluctance Motor (SRM), are investigated. Since radial force causes stator vibrations and noise caused by magnetic field, a new switched reluctance motor model with increased stator and rotor poles has been designed in order to reduce the radial force acting on the rotor poles. In addition, a structure with high torque and low leakage flux compared to conventional winding structure has been proposed for Switched Reluctance Motors (SRM). The windings of the designed SRM are placed in layers, insulated from each other. Rotor poles are formed to move on both sides of each phase winding. Thus, the flux that will occur in the phase windings axially completes its circuit from the stator poles and the rotor poles. This designed ARM model has been examined by Finite Element Method (FEM. The proposed motor geometry has been analyzed with ANSYS Maxwell-3D, which performs FEM-based solution), and parametric analysis with ANSYS-RMxprt.